Outcome of a-Blockers, with and without Corticosteroid Combination, in Medical Expulsive Therapy for Lower Ureteric Stones - Muhammad Omer, Maaz Shahid, Syed Muhammad Hassan Akhtar, Hafiz Muhammad Mohsan Iqbal, Muhammad Asif, Mufassar Nishat, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary calculi have serious implications in urology. Lower ureteral stones can cause obstructive uropathy and subsequent deterioration of renal function. Because the patient’s symptoms and stone size do not predict loss of renal function and because there is no clear time threshold for irreversible damage, treatment should be strongly considered in any patient with ureteral stones. In this study we are comparing the results of medical expulsive therapy using alpha blockers with vs, without combination of corticosteroids as adding steroids increases the efficacy by decreasing stone expulsion time. Keywords: Ureteric calculi, stone clearance, stone expulsion time, medical expulsive therapy.